Role of N-Nitro-L-Arginine-Methylester in Neuroprotection of Cerebral Ischemic Preconditioning in Rats (Asian Journal of Pharmaceutics (AJP), 2020)
Background and Aim: Ischemic preconditioning (IPC) is a phenomenon in which brief episodes of ischemiaprotect the brain from subsequent, severe ischemic insult. This study evaluated whether the neuroprotective effect ofcerebral IPC is mediated by nitric oxide synthase (NOS) inhibition, using non-selective NOS inhibitor, and N-Nitro-L-Arginine-Methylester (L-NAME). Materials and Methods: Fifty adult male Wistar rats divided into five groupsten in each: (1) Sham-operated group (control), (2) ischemia-reperfusion (I/R) group; rats subjected to 30 min ofleft common carotid artery (CCA) occlusion followed by 24-h of reperfusion, (3) I/R with NOS inhibition group;rats infused with L-NAME intraperitoneally 15 min before the same I/R period, (4) IPC group; rats treated withthree 5-min episodes of CCA occlusion (CCAO) with 10 min of reperfusion between stimuli, then 30 min of CCAOfollowed by 24 h reperfusion, and (5) IPC with NOS inhibition group: Rats were subjected to the same preconditioningstimuli as Group 4 with the infusion of NOS inhibitor (L-NAME) 15 mg/kg, 15 min before CCAO. Neurologicalassessments were evaluated, enzyme-linked immunosorbent assay used to detect Rho-kinases (ROCK), and nitricoxide metabolites were measured colorimetrically. Results: IPC significantly reduces the neurological deficitand lowering the ROCK level with higher nitrite levels. While administration of L-NAME in IPC rats results in asignificant enhancement in neurological scoring compared to IPC without NOS inhibition, with significant inhibitionof nitrite and ROCK. Conclusion: Despite previous evidence that NO involves in neuroprotective mechanism ofIPC, the current data suggest the potential ofL-NAME as a neuroprotective component of IPC.